Pemanfaatan Platform Merdeka Mengajar terhadap Kompetensi Pedagogik Guru di SMAN 1 Airpura - Sari, Nora Maita; Novrianti, Novrianti; Zen, Zelhendri; Rahmayanti, Elsa (Indo-MathEdu Intellectuals Journal, 2024)
The curriculum changes that occur are a challenge for teachers in their implementation. Therefore, the Ministry of Education and Culture launched the Independent Teaching Platform with the aim of helping teachers in understanding and implementing the Independent Curriculum. This study aims to determine the use of the Independent Teaching Platform on the pedagogic competence of teachers at SMA Negeri 1 Airpura. This research is a type of evaluative research with a quantitative descriptive approach. The sample in this study amounted to 49 people. The data analysis in this study was carried out descriptively. The results of the research on the use of the Merdeka Mengajar platform on the pedagogic competence of teachers at SMA Negeri 1 Airpura, with a percentage of questionnaire results of 74% on the Inspiration Video feature, 79% on the Independent Training feature, 76% on the Proof of Work feature, 73% on the Student Assessment feature, and 80% on the Teaching Tool feature, it can be concluded that this platform has played a significant role in supporting the development of teachers' pedagogic competence. Overall, this study shows that the Merdeka Teaching platform has been well utilized by teachers at SMA Negeri 1 Airpura. However, there are still several aspects that need to be improved to ensure that all features can be used optimally by all teachers, so that they can be more maximal in improving their pedagogic competence